Personalized Remote Healthcare Monitoring System - Tasic, Jurij; Madevska Bogdanova, Ana; Simjanoska, Monika; Koteska, Bojana (MIDEM - Society for Microelectronics, Electronic Components and Materials, 2021)
In the paper, the personalized remote healthcare monitoring system (RHMS), that could be used to monitor patients at their home rather than in a hospital, thus reducing resources on hospital facilities and medical staff, is presented. An example of a pilot personalized remote healthcare system is demonstrated, including realized solution.